Voicing the voiceless: unraveling the Master/Slave relationship in Nadine Gordimer's July's People - Majeed, Abdulhameed A.; Singh, Hardev Kaur Jujar (International Institute for Science, Technology and Education, 2018)
This article examines the Master/Slave relationship in Nadine Gordimer’s July’s People using stylistics. The novel is set in a village for the black people. July, the black servant, hides the white family, the Smales, from the black people. There has been a revolution against the white people and their apartheid system. The novel traces July’s development in his relationship with the Smales. During the novel, we witness a major change in July’s attitude towards the Smales. The old Master/Slave relationship has changed drastically. July seizes the tools of power from the white family. In this article, I’m going to trace July’s development and how he has managed to shake the foundation of the Master/Slave relationship. Moreover, I’m going to follow a textual analysis of the novel using Michael Toolan’s analysis of conversation in fiction. His analysis will count for the changes that occur for July.